The role of European age-group championships in senior participation rates - Hanley, B. (New Studies in Athletics, 2016)
The European Athletics U20and U23 Championships are important steps in the career path of talented young athletes. Previous studies have examined how well the very best athletes from these age group championships perform in subsequent high-level competition, including the Olympic Games and IAAF World Championships in Athletics. But these events also play an important role in simply retaining talented young athletes through to the senior level, which is of interest to the wider athletics community. This study aimed to evaluate the impact of the two championships by means of a detailed analysis of the overall participation rates in the post-junior careers of talented athletes. It included examination of the differences between disciplines and nations. The results show that the two championships improve the chances that those who take part will continue competing as seniors, and that the U23 championships are particularly effective in maintaining participation between the ages of 25 and 29. The study concludes with a number of recommendations to Member Federations for supporting young athletes in their transition to the senior ranks. (siehe auch unter https://www.researchgate.net/publication/316991094)